FORMULASI DAN EVALUASI KAPSUL VITAMIN D2 DARI EKSTRAK ETANOL 96% JAMUR SAWIT (Volvariella volvacea) DENGAN MENGGUNAKAN METODE GRANULASI BASAH: FORMULATION AND EVALUATION OF VITAMIN D2 CAPSULES FROM 96% ETHANOL EXTRACT OF PALM MUSHROOM (Volvariella volvacea) USING WET GRANULATION METHOD - Risqa Aulia; Oky Hermansyah; Dwi Kurnia Putri; Rose Intan Perma Sari; Suci Rahmawati (JFL : Jurnal Farmasi Lampung, 2026)
Abstract This study investigates the use of a 96% ethanol extract of palm mushroom (Volvariella volvacea) as a source of vitamin D₂ in a capsule dosage form using the wet granulation method to improve stability. The aim was to formulate and evaluate granule and capsule characteristics in accordance with pharmacopeial standards. This experimental study used three formulations (F0, F1, and F2). Evaluations included organoleptic properties, moisture content, flow rate, angle of repose, weight uniformity, disintegration time, and vitamin D₂ content. The extract yield was approximately 10%. Granules met the requirements for moisture content and angle of repose, but flow rate decreased with higher extract concentration. Capsules met the requirements for weight uniformity and disintegration time (3–8 minutes). The highest vitamin D₂ content was found in F2, while F1 showed the best balance between physical properties and active content. In conclusion, wet granulation produced capsules that met quality requirements, with F1 as the optimal formulation. Keywords:  Vitamin D2, Palm mushroom, Wet granulation, Capsules, Formulation